Improvement in Cognitive Function Through Brain Gymnastics For Nursing Home Residents: A Quasi-Experimental Study from Indonesia - Siska Evi Martina; Rumondang Gultom; Janno Sinaga; Agustina Hia (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Cognitive function in older adults is influenced by various factors, including age, gender, education, and physical activity, all of which can contribute to cognitive decline. This decline poses a growing challenge, particularly among institutionalized elderly populations. Brain gymnastics, a simple, low-cost, non-pharmacological intervention, has shown potential for improving cognitive function, yet evidence among nursing home residents remains limited and inconsistent. This study aimed to evaluate the effect of brain gymnastics on cognitive function among older adults residing in nursing homes in North Sumatera. A quasi-experimental design was employed, involving 56 participants aged 60 to 80 years, divided into intervention (n = 28) and control (n = 28) groups through purposive sampling. The intervention group engaged in a four-week brain gymnastics program, while the control group received a self-guided exercise leaflet. The study was conducted from January to March 2025. Cognitive function was assessed using the MoCA-INA at baseline and post-intervention. Descriptive statistics, Chi-square tests, paired t-tests, and independent t-tests were used for data analysis. At baseline, both groups exhibited moderate cognitive function (62.5% and 67.9%, respectively). Post-intervention, the intervention group showed a significant improvement in mean cognitive scores from 17.64 ± 4.09 to 22.00 ± 4.46 (p < 0.001, Cohen's d = 1.52), whereas the control group demonstrated a smaller increase. An independent t-test revealed a significant difference in post-intervention scores between the intervention (22.00 ± 4.46) and control (17.00 ± 3.23) groups (p < 0.001, Cohen's d = 3.89), indicating a strong effect of the intervention. These findings underscore the potential of brain gymnastics as a practical, scalable, and cost-effective strategy to enhance cognitive health. Its integration into routine elderly care may help delay cognitive decline and promote healthier aging, particularly in low-resource settings. Keywords: Brain Gymnastic, Older People, Cognitive Function, Nursing Home